Time for a Differentiated Method for Intercultural Negotiations ? Research on the Universal Applicability of Getting to Yes - Ratt, Yannic (Department of Public Law, 2024)
Existing negotiation literature attempts to provide readers with guidance on how to negotiate successfully, but does not take into account the increasing complexity of inter-cultural negotiations. To facilitate inter-cultural negotiations, this dissertation explored the universal applicability of the book Getting to Yes: Negotiating an Agreement without Giving In1 by Roger Fisher, William Ury and Bruce Patton, which has paramount significance in the negotiation literature, and ultimately proposed a differentiated method. Without a new perspective on the existing negotiation literature that promotes universal applicability, intercultural negotiations are repeatedly based on a false basic premise and an important further development of negotiation methodology is blocked. This dissertation therefore examined the universal applicability of the Getting to Yes method based on existing literature and made suggestions as to which approaches should be used in inter-cultural settings instead. As a result, this dissertation shows the reader the difficulties of inter-cultural negotiations and that not a uniform but a differentiated method is necessary to conduct them in a promising way. Accordingly, the proposed differentiated method can contribute to this.